Senior High School Students’ Perception of the Use of Chatgpt in Learning English Vocabulary: Persepsi Siswa Sekolah Menengah Atas terhadap Penggunaan ChatGPT dalam Pembelajaran Kosakata Bahasa Inggris - Ayu Dewanti; Yeni Rahmawati; Ibrahim (Language Development Center, 2026)
Background: The rapid development of generative artificial intelligence, particularly ChatGPT, has influenced educational practices in English as a Foreign Language (EFL) learning. While ChatGPT may support vocabulary learning, concerns regarding accuracy, trust, motivation, and ethical use remain, particularly at the secondary school level. Purpose: This study aims to examine senior high school students’ perceptions of ChatGPT as a tool for learning English vocabulary, focusing on perceived usefulness, ease of use, accuracy and trust, motivation, ethical concerns, and gender-based differences. Method: This study employed a quantitative survey design involving 224 eleventh-grade students from a public vocational high school in Indonesia. Data were collected using a structured questionnaire adapted from previously validated instruments and analyzed through descriptive statistics and independent-samples t-tests. Results and Discussion: The findings indicate that students’ perceptions of ChatGPT were moderate across all constructs, with mean scores ranging from 2.67 to 3.13. ChatGPT was perceived as easy to use (M = 3.13) and useful (M = 3.10) for English vocabulary learning, whereas perceptions of accuracy and trust were lower (M = 2.67), reflecting cautious attitudes toward AI-generated content. Gender-based analysis revealed significant differences in ease of use and accuracy/trust, with male students reporting higher mean scores (Ease of Use: M = 3.20; Accuracy/Trust: M = 2.79) than female students (Ease of Use: M = 3.02; Accuracy/Trust: M = 2.51). No significant gender differences were found in usefulness, motivation, or ethical concerns. Conclusions and Implications: This study concludes that ChatGPT can serve as a supplementary tool for EFL vocabulary learning when used pedagogically and responsibly. Conducted among grade 11 students in Indonesia, the findings emphasize the importance of teacher guidance, ethical awareness, and AI literacy. Future studies are recommended to examine broader contexts and additional factors infuencing AI-assisted language learning.